Detectable Unmetabolized Folic Acid and Elevated Folate Concentrations in Folic Acid-Supplemented Canadian Children With Sickle Cell Disease - Williams, Brock A.; Mayer, Cara; McCartney, Heather; Devlin, Angela M.; Lamers, Yvonne; Vercauteren, Suzanne M.; Wu, John K.; Karakochuk, Crystal D. (Frontiers in Nutrition, 2021)
Sickle cell disease (SCD) is an inherited hemoglobinopathy caused by a variant (rs344) in the HBB gene encoding the β-globin subunit of hemoglobin. Chronic hemolytic anemia and increased erythropoiesis and RBC turnover in individuals with SCD can result in increased needs for folate and other B-vitamins. We assessed B-vitamin status, and the distribution of folate forms, including unmetabolized folic acid (UMFA), in Canadian children with SCD supplemented with 1 mg/d folic acid (current routine practice). Non-fasted serum and plasma samples were analyzed for concentrations of folate, and vitamins B-2, B-6, and B-12. Eleven individuals (45% male; SCD type: HbSS n=8, HbSC n=2, HbSβ0-Thal n=1), with a median (IQR) age of 14 (7, 18) years, were included. Total folate concentrations were 3 to 27 times above the deficiency cut-off (10 nmol/L), and 64% of children had elevated folate levels (>45.3 nmol/L). UMFA (>0.23 nmol/L) was detected in all children, and 36% of participants had elevated levels of UMFA (>5.4 nmol/L). All children were vitamin B-12 sufficient (>150 pmol/L), and the majority (55%) had sufficient B-6 status (>30 nmol/L). Among this sample of Canadian children with SCD, there was limited evidence of B-vitamin deficiencies, but UMFA was detectable in all children.